2020
DOI: 10.1002/hrm.22051
|View full text |Cite
|
Sign up to set email alerts
|

Hello again: Managing talent with boomerang employees

Abstract: Boomerang employees—previous employees who return to an organization after an absence—offer unique value in the talent pool, representing external employees with internal job experience. Utilizing a sample from a professional services firm in the United States, we draw from the literature on talent management and renegotiated psychological contracts to compare the compensation, satisfaction, commitment, and performance of boomerangs to similar employees who never left the firm. We find that reentry yields impr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 109 publications
(179 reference statements)
1
8
0
Order By: Relevance
“…Our findings add to the scant research on short‐term inter and intrafirm mobility, such as the literature on secondments (Hoenen & Kolympiris, 2020; Kolympiris et al, 2019; Wang et al, 2010), short‐term intrafirm mobility (Choudhury, 2017) and boomerang employees (Keller et al, 2020; Snyder et al, 2021). This literature has focused on the advantages and challenges of short‐term mobility events for the individual and the sending unit after the individual returns.…”
Section: Discussionsupporting
confidence: 61%
“…Our findings add to the scant research on short‐term inter and intrafirm mobility, such as the literature on secondments (Hoenen & Kolympiris, 2020; Kolympiris et al, 2019; Wang et al, 2010), short‐term intrafirm mobility (Choudhury, 2017) and boomerang employees (Keller et al, 2020; Snyder et al, 2021). This literature has focused on the advantages and challenges of short‐term mobility events for the individual and the sending unit after the individual returns.…”
Section: Discussionsupporting
confidence: 61%
“…Since rehiring is an under-observed recruitment method in research, there is still an extreme lack of study about this topic ( Arnold et al, 2021 ). Moreover, most related studies focused on the attitude, behavior, and performance of boomerang employees after being rehired ( Swider et al, 2017 ; Arnold et al, 2021 ; Maier et al, 2021 ; Snyder et al, 2021 ). Although Shipp et al (2014) and Raveendra and Satish (2021) focused on the antecedents and processes before the rehiring.…”
Section: Discussionmentioning
confidence: 99%
“…However, most of the related studies focused on the attitude, behavior, and performance of boomerang employees after being rehired. Specifically, Arnold et al (2021) studied the job performance and turnover rate of the ex-employees after they have been rehired; Snyder et al (2021) showed the psychological contract reconstruction and the resulting improvement in compensation, satisfaction, organizational commitment, extra-role/in-role behaviors, and performance of boomerang employees after they have been rehired; Maier et al (2021) showed that boomerang employees who have returned to a previous employer consider their new situation better than the first time; Swider et al (2017) extend a careers-based learning perspective to construct a theoretical framework of a set of factors that influence boomerang employee return performance. Although Shipp et al (2014) and Raveendra and Satish (2021) focused on the antecedents and processes before the rehiring.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, this research has helped to clarify the psychological process that people most involved in the organisation go through, and it has helped to advance the importance of the psychological contract (Snyder, Stewart & Shea, 2020). Moreover, this work has aided understanding of how involvement is related to other attitudes (Truss, Shantz, Soane, Alfes & Delbridge, 2013) and how this involvement is linked to employees' recognition and demands in organisations.…”
Section: Theoretical Implicationsmentioning
confidence: 96%